Customer Relationship Management in Digital Marketing and Its Impact on Customer Satisfaction, Loyalty, and Profitability - Daimah Daimah (Journal of Business, Social and Technology, 2025)
Background: In the digital marketing era, Customer Relationship Management (CRM) is widely adopted to improve customer satisfaction, loyalty, and profitability. However, CRM implementation often emphasizes technology while neglecting service quality and relational processes, resulting in transactional relationships rather than long-term customer engagement. Therefore, examining the combined role of CRM and service quality in influencing customer outcomes remains important. Objective: This study analyzes the relationship between CRM implementation, service quality, customer satisfaction, customer loyalty, and profitability at PT. Syntax Corporation Indonesia through its parent company, Riviera Publishing. Methods: This research employed a seven-step scientific methodological approach. Data were collected through structured interviews and surveys involving marketing team representatives implementing a digital-based CRM system. The study examined four main variables: CRM practices (human resources, processes, and technology), service quality, customer satisfaction, and customer loyalty, as well as their impact on company profitability. Results: The findings indicate that CRM implementation does not have a significant effect on customer satisfaction, as reflected by the dominance of one-time transactions and limited utilization of customer databases for long-term relationship building. In contrast, service quality has a significant positive effect on customer loyalty, while CRM practices positively influence company profitability through improved marketing efficiency. Conclusion: CRM implementation alone does not significantly enhance customer satisfaction but contributes positively to profitability, whereas service quality plays a crucial role in strengthening customer loyalty. These results emphasize the importance of integrating CRM systems with effective service quality management to achieve optimal customer relationship outcomes in digital marketing contexts.